Formulation and psysicochemical characterization of starch-based films for potential packaging applications - Gilongos, Pauline Ysabelle A.; Marero, Emylle Dawn B.; Villamora, Maria Angela M.
Bio-based films have gained attention as sustainable alternatives to conventional plastic packaging. However, their commercial adoption is limited due to poor mechanical strength and high-water permeability. This study aimed to develop and evaluate the potential of a starch-based film using tapioca starch, glycerin, citric acid, and silicon dioxide (SiO2). Mechanical performance of films was determined using the folding test, tensile strength, and elongation at break while hydrophobicity was evaluated by measuring moisture content, water uptake, water solubility, and water vapor transmission rate (WVTR).